Application of small-sized magnetically controlled capsule gastroscopy in upper gastrointestinal diseases screening in asymptomatic individuals - Xu, Yan; Li, Siquan; Ye, Zhanhui; Liang, Xiue; Zhang, Weizheng; He, Hongzhen; Li, Jun; Liu, Na; Cai, Xiangsheng; Chen, Kequan (Surgical endoscopy, 2024)
Objective To explore the application of small-sized magnetically controlled capsule gastroscopy (MCCG) in upper gastrointestinal diseases screening in asymptomatic individuals. Methods A retrospective analysis of the clinical data of 2163 asymptomatic individuals who underwent small-sized MCCG at our center from September 2022 to December 2023. The detection of submucosal tumors, polyps and ulcers in the upper gastrointestinal tract, the tolerance and safety of the subjects were statistically analyzed. Results Suspected submucosal tumors in the upper gastrointestinal tract were detected in 34 (1.57%) of 2136 subjects, with a higher incidence in females and no observed age difference. Polyps were detected in 328 subjects (15.16%), with a higher incidence in females and an increased detection rate with increasing age. Ulcers were detected in 27 subjects (1.25%), with a higher incidence in males and no observed age difference. There was no significant discomfort in all subjects, and no adverse event or capsule retention occurred. Conclusion Small-sized MCCG can be used for focal lesion screening in the upper gastrointestinal tract and is comfortable and safe, making it a safe and efficient method for examining upper gastrointestinal diseases in the physical examination population.